Numerical solution of the problem of spatially loaded rods in linear and geometrically nonlinear statements - Shahzoda Amanbayevna, Anarova; Faxriddin Murodillayevich, Nuraliyev; Botir Shukurillayevich, Usmonov; Shohruh Ibodullayevich, Chulliyev (International Journal of Engineering and Technology, 2018)
The article deals with the numerical solution of the problem of spatially loaded rods in linear and geometrically nonlinear statements. The results are presented in the form of graphs. A description of the results obtained and a comparative analysis of all parameters of the task set are given. A comparative analysis between linear and non-linear results is conducted. The aim of problem investigated the statics and dynamics of linear and geometrically nonlinear problem of stress-strain state of rods under spatial loading and the objects of problem are strained processes in linear and geometrically nonlinear problem of the statics and dynamics of rods under spatial loading are given.Â